Effects of arbuscular mycorrhizal fungi on the reduction of arsenic accumulation in plants: a meta-analysis - Hao, Shangyan; Tian, Ye; Lin, Zhiqing; Xie, Linzhi; Zhou, Xinbin; Bañuelos, Gary S. (Frontiers in Plant Science, 2024)
Arsenic (As) accumulation in plants is a global concern. Although application of arbuscular mycorrhizal fungi (AMF) has been suggested as a potential solution to decrease As concentration in plants, there is currently a gap in a comprehensive, quantitative assessment of the abiotic and biotic factors influencing As accumulation. A meta-analysis was performed to quantitatively investigate the findings of 76 publications on the impacts of AMF, plant properties and soil on As accumulation in plants. Results showed a significant dose-dependent As reduction with higher mycorrhizal infection rates, leading to a 19.3% decrease in As concentration. AMF reduced As(V) by 22.92%, but increased dimethylarsenic acid (DMA) by 50.8%. AMF significantly decreased grain As concentration by 34.1%. AMF also improved plant P concentration and dry biomass by 33.0% and 62.0%. The most significant reducing effects of As on AMF properties were seen in single inoculation and in experiments with intermediate durations. Additionally, the benefits of AMF were significantly enhanced when soil texture, soil organic carbon (SOC), pH level, Olsen-P and DTPA-As were sandy soil, 0.8-1.5%, ≥7.5, ≥9.1 mg/kg and 30-60 mg/kg, respectively. AMF increased easily-extractable glomalin-related soil protein (EE-GRSP) and total glomalin-related soil protein (T-GRSP) by 23.0% and 28.0%. Overall, the investigated factors had significant implications in developing AMF-based methods for alleviating the negative effects of As stress on plants.